Finite element modelling of Erichsen Olsen sheet metal formability test - Islahuddin Idha, Nawawi (2009)
The main objective of this project is to assess the characteristic and formability of sheet metal to withstand plastic deformation without rupture using finite element method or to be more specific using ALGOR software with Olsen-Erichsen Test. Olsen-Erichsen Test is the one of the most popular technique since it is the method that used long before compare with other method. In this test there is a variable that being manipulate which are the element definition and type of material like aluminium, magnesium and brass. Meanwhile the variable that constant is the size dimension. After the drawing drawn in ALGOR software fill in the information needed to run the simulation and the data needed is collected. Through the data, the graph of displacement deformation between axis Z and Y is plotted. The data is analyse and found that magnesium is the most ductile followed by aluminium and brass. From the research data, it can be verify using the information in table of material properties to check the result from simulation is right or not.